Enter your EMAIL address BELOW for JOKES by EMAIL once a WEEK!

Sponsored Links 


N equals N plus one
Theorem: n=n+1
Proof:
(n+1)^2 = n^2 + 2*n + 1
Bring 2n+1 to the left:
(n+1)^2  (2n+1) = n^2
Substract n(2n+1) from both sides and factoring, we have:
(n+1)^2  (n+1)(2n+1) = n^2  n(2n+1)
Adding 1/4(2n+1)^2 to both sides yields:
(n+1)^2  (n+1)(2n+1) + 1/4(2n+1)^2 = n^2  n(2n+1) + 1/4(2n+1)^2
This may be written:
[ (n+1)  1/2(2n+1) ]^2 = [ n  1/2(2n+1) ]^2
Taking the square roots of both sides:
(n+1)  1/2(2n+1) = n  1/2(2n+1)
Add 1/2(2n+1) to both sides:
n+1 = n
Visit the previous joke about this topic!
Return to the math jokes page
Search for Jokes by Keyword 

